Instance segmentation ship detection based on improved Yolov7 using complex background SAR images - Yasir, Muhammad; Zhan, Lili; Liu, Shanwei; Wan, Jianhua; Hossain, Md Sakaouth; Isiacik Colak, Arife Tugsan; Liu, Mengge; Islam, Qamar Ul; Raza Mehdi, Syed; Yang, Qian (Frontiers in Marine Science, 2023)
Instance segmentation is more difficult than object identification and semantic segmentation in high-resolution remote sensing images. Predicting class labels and pixel-wise instance masks is the goal of this technique, which is used to locate instances in images. Despite this, there are now just a few methods available for instance segmentation in high-resolution remote sensing (HR-RS) data, where a remote-sensing image's complex background makes the task more difficult. This research proposes a unique method for Yolov7-improving HR-RS image segmentation one-stage detection. First, we redesigned the structure of the one-stage fast detection network to adapt to the task of ship target segmentation and effectively improve the efficiency of instance segmentation. Secondly, we improve the backbone network structure by adding two feature optimization modules, so that the network can learn more features and have stronger robustness. In addition, we further modify the network feature fusion structure, improve the module acceptance domain to enhance the prediction ability of multi-scale targets, and effectively reduce the amount of model calculation. Finally, we conducted extensive validation experiments on the sample segmentation data sets HRSID and SSDD. The experimental comparisons and analyses on the HRSID and SSDD datasets show that our model enhances the predicted instance mask accuracy, enhancing the instance segmentation efficiency of HR-RS images, and encouraging further enhancements in the projected instance mask accuracy. The suggested model is a more precise and efficient segmentation in HR-RS imaging as compared to existing approaches.